2008
DOI: 10.5860/crl.69.6.493
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Student and Faculty Needs through LibQUAL+™: An Analysis of Qualitative Survey Comments

Abstract: The LibQUAL+™ survey allows libraries to collect quantitative as well as qualitative data concerning their users. Comments that survey-takers provide contain a wealth of information that shed light on the quantitative responses they give to questions. This article reports on a study conducted by the authors to analyze the written comments provided by faculty and students participating in the 2006 LibQUAL+™ survey at the University of Notre Dame to determine, in a systematic way, what issues are most important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Of the articles identified, only three (Jones and Kayongo, 2008;Washburn, 2013;Habich, 2008) reported using Excel as the primary tool for performing qualitative analysis. Qualitative analysis projects by Jones and Kayongo and Washburn used multiple coders and describe attempts to increase objectivity by redundant review of comment data and coder negotiations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the articles identified, only three (Jones and Kayongo, 2008;Washburn, 2013;Habich, 2008) reported using Excel as the primary tool for performing qualitative analysis. Qualitative analysis projects by Jones and Kayongo and Washburn used multiple coders and describe attempts to increase objectivity by redundant review of comment data and coder negotiations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 Sherri Jones and Jessica Kayongo, in their 2008 study of student and faculty needs highlighted by 2006 LibQUAL+ data, found that most of the written comments coming from faculty addressed the Information Control area measured by LibQUAL+. 6 Bruce Thompson, Martha Kyrillidou, and Colleen Cook note that responses to questions about information control show high expectations across faculty, graduate student, and student groups, and point to the increasing importance of digital collections and online tools for an increasing number of library users, and note that when faculty rank library services by importance, they consistently place services aligning with information control in the top five most important, unlike undergraduate students responding to LibQUAL+. 7 LibQUAL+ research shows the emerging importance of information control for all user groups, but it is of specific concern when looking at library services to faculty.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…Among all assessment methods, surveys are one of the most frequently used instruments by libraries to measure user behaviors, attitudes, perceptions and experiences (Liebst and Feinmark, 2016). The literature is rich with studies assessing the needs and satisfaction of users, related to library services and resources, through surveys (Jones and Kayongo, 2008; Jankowska et al , 2006; Kayongo and Helm, 2010; Line, 1963, 1966; Maughan, 1999).…”
Section: Introductionmentioning
confidence: 99%